Anti-oxidation coated SmFeN powder as well as coating method and application thereof

By using dibutyl hydroxytoluene and zirconium coupling agent to form a stable electric double layer structure during the ball milling of SmFeN powder, the problems of easy oxidation and complex process of SmFeN powder are solved, and efficient anti-oxidation coating is achieved, and production costs are reduced. And improves magnetic performance and safety.

CN119296936APending Publication Date: 2025-01-10HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310838777.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing SmFeN permanent magnet material preparation process has problems such as heterophasic generation, high cost, complex process, and easy oxidation of powders, especially during the ball milling process, which is difficult to effectively prevent oxidation.

Method used

SmFeN powder was added in batches during ball milling using dibutyl hydroxytoluene and zirconium coupling agents to control the concentration of dibutyl hydroxytoluene below 0.02 wt%, forming a stable electric double layer structure, reducing powder activity and promoting inorganic matter Combined with organic matter to avoid oxidation reactions.

Benefits of technology

It significantly improves the coating effect of the anti-oxidation layer on the surface of SmFeN powder, reduces production costs, simplifies the process flow, improves product safety and magnetic properties, and is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004329841150000131
    Figure BDA0004329841150000131
Patent Text Reader

Abstract

The invention provides anti-oxidation coated SmFeN powder as well as a coating method and application thereof. The coating method comprises the steps of material taking, material adding, ball milling, material discharging and drying which are carried out in sequence, materials related to the material taking comprise SmFeN powder prepared by a reduction diffusion method, butylated hydroxytoluene and a zirconium coupling agent, and the SmFeN powder is prepared by the reduction diffusion method; the step of feeding comprises the step of adding SmFeN powder into a ball mill; the ball milling comprises the step of adding butylated hydroxytoluene and a zirconium coupling agent into a ball mill in batches, and the concentration of the butylated hydroxytoluene in the ball-milled material in each batch is less than or equal to 0.02 wt%. The coating method provided by the invention can be used for coating fine SmFeN powder, and on the premise of ensuring the performance of SmFeN, dangers in the production process are avoided, the preparation process is simplified, the production cost is reduced, and large-scale popularization and application are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic materials, and relates to an anti-oxidation coated SmFeN powder, and in particular to an anti-oxidation coated SmFeN powder and a coating method and application thereof. Background Art

[0002] SmFeN material has gradually become the most valuable permanent magnet material after NdFeB due to its advantages such as high Curie temperature, good temperature and chemical properties, and low price. In recent years, research on the preparation of SmFeN permanent magnet materials has mainly focused on powder metallurgy, mechanized alloying, rapid quenching, and reduction diffusion. The smelting method and rapid quenching method are prone to the generation of impure α-iron in the process of preparing metal alloys, and require long-term ball milling, which is costly and has irregular particle morphology after ball milling, thus adversely affecting product performance. The reduction diffusion method uses metal Ca or CaH 2 , CaCl 2 Mix with cheap metal oxide or metal chloride raw materials and metal raw materials such as Fe, and heat them in high temperature Ar or N 2 In the atmosphere, using metal Ca or CaH 2 The strong reducing property of SmFeN powder can react with metal oxides to form the required alloy products. Similar to sintered NdFeB, the particle size of SmFeN powder has a great influence on its performance. If the powder is too coarse, it will have a significant impact on the coercive force and orientation. If the powder is too fine, it will cause severe oxidation, which will lead to a significant reduction in magnetic properties and mechanical strength.

[0003] In addition, in the preparation methods of rare earth permanent magnet alloys, the rapid quenching method, powder metallurgy method and hydrogen crushing method all have the problems of complex process, long cycle, high energy consumption and difficulty in industrial production. The powder material structure obtained by the high-energy ball milling method is disordered, and in addition to the SmFeN phase, the powder also contains many impurities. The powder obtained by the reduction diffusion method has less SmFeN impurity phase, but due to the production process, the obtained products are all blocky and contain Ca element compounds and Ca residues. Ball milling is required for subsequent crushing, and the material will release a lot of heat during the ball milling process. The powder is easily oxidized and even burns, which is not conducive to subsequent drying.

[0004] CN105702407A discloses a method for preparing a magnetic ceramic-coated SmFeN permanent magnet material. The invention is to mix ferrous chloride, butyl titanate and other substances, heat in a water bath, and concentrate to obtain a ceramic intermediate gel, then mix samarium powder and iron powder for smelting, anneal and ball-mill to form metal powder, and wrap the bonding metal powder with the ceramic intermediate gel with magnetic surface, and perform composite firing to obtain a magnetic ceramic-coated SmFeN permanent magnet material. However, the preparation process of the invention is too complicated, the production cost is high, and there is still a lot of room for improvement.

[0005] CN114156033A discloses a SmFeN powder and a preparation method thereof, wherein the surface of the SmFeN powder is coated with a phosphating film, and the preparation method comprises the following steps: mixing Sm powder, Fe powder, anionic surfactant, phosphating liquid and ammonia-containing liquid for high-energy ball milling, and drying the slurry separated after the high-energy ball milling to obtain SmFeN powder. The invention achieves powder coating before drying of the SmFeN powder by adding anionic surfactant and phosphating liquid in the high-energy ball milling method to form a dense protective film, thereby ensuring the activity and magnetism of the product and eliminating the potential safety hazards in the production process. However, the ammonia nitrogen content of the medium increases during the ball milling process, and excessive alkalinity will affect the formation of the protective film.

[0006] It can be seen that how to provide an anti-oxidation coated SmFeN powder and a coating method thereof, to coat finer SmFeN powder, to ensure the performance of SmFeN while avoiding danger in the production process, simplifying the preparation process, and reducing production costs has become an urgent problem that technicians in this field need to solve. Summary of the invention

[0007] The purpose of the present invention is to provide an oxidation-resistant coated SmFeN powder and a coating method and application thereof. The coating method can coat finer SmFeN powder, while ensuring the performance of SmFeN, avoiding dangers in the production process, simplifying the preparation process, reducing production costs, and facilitating large-scale promotion and application.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a coating method for anti-oxidation coated SmFeN powder, the coating method comprising taking material, adding material, ball milling, discharging material and drying in sequence.

[0010] The materials involved in the material collection include SmFeN powder, dibutyl hydroxytoluene and a zirconium coupling agent, and the SmFeN powder is prepared by a reduction diffusion method.

[0011] The adding includes adding SmFeN powder into a ball mill.

[0012] The ball milling includes adding butylated hydroxytoluene and a zirconium coupling agent into a ball mill in batches, and the concentration of butylated hydroxytoluene in each batch of ball milled materials is ≤0.02wt%, for example, it can be 0.002wt%, 0.004wt%, 0.008wt%, 0.01wt%, 0.012wt%, 0.014wt%, 0.016wt%, 0.018wt% or 0.02wt%, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0013] The present invention controls the concentration of each batch of butylated hydroxytoluene in the ball-milled material to be below 0.02wt%, which is beneficial to significantly improve the coating effect of the anti-oxidation layer on the surface of the SmFeN powder. When the concentration is higher than 0.02wt%, phenol odor will be introduced and the coating effect will be adversely affected.

[0014] In the present invention, butylated hydroxytoluene is added to SmFeN powder during the ball milling process. In the phenolic hydroxyl group COH structure on the benzene ring, the oxygen atom contains a lone pair of p electrons, and the p electron cloud and the large π electron cloud of the benzene ring overlap from the side, so that the p electron cloud on the oxygen atom is transferred to the benzene ring, and the electron cloud between the hydrogen and oxygen atoms is transferred to the direction of the oxygen atom. As a result, the CO bond is more solid, the OH bond is easier to break, and the hydrogen in the hydroxyl group is easier to ionize.

[0015] In addition, there are two strong electron-pushing groups at the 2.6 position of butylated hydroxytoluene, which shows a negative electric field to the outside. The SmFeN powder obtained by the reduction diffusion method has residual ferrous ions, samarium ions and calcium oxide on the surface. The hydrogen ions ionized by butylated hydroxytoluene will react with the residual calcium hydroxide in water to neutralize. Ferrous ions, samarium ions and calcium ions make the surface of SmFeN powder particles positively charged. After butylated hydroxytoluene combines with them, it forms a stable system with a double electric layer structure, thereby reducing the activity of the powder and preventing it from reacting violently after contacting the air.

[0016] Furthermore, the present invention adds a zirconium coupling agent to the SmFeN powder during the ball milling process, which significantly promotes the full combination of inorganic and organic matter, because if butylated hydroxytoluene is better coated on the powder surface, a coupling agent is needed to improve the combination of inorganic and organic. Compared with traditional silane coupling agents, the inorganic part of the zirconium coupling agent has a large specific gravity, which significantly reduces the viscosity of the powder after coating, thereby improving the fluidity of the powder. In addition, due to the high metallicity of the zirconium coupling agent, the binding force between butylated hydroxytoluene and the metal is greatly increased.

[0017] In the present invention, the reduction diffusion method is a conventional method used by those skilled in the art to prepare SmFeN powder. As long as the SmFeN powder can be successfully prepared, its specific preparation conditions are not particularly limited herein. For example, the preparation method disclosed in CN1424165A can be used to prepare SmFeN powder.

[0018] Exemplarily, the reduction diffusion method specifically includes: using metal Ca or CaH 2 , CaCl 2 Calcium compounds such as calcium are mixed with cheap metal oxides or metal chloride raw materials and metal raw materials such as Fe, and heated in high temperature Ar or N 2 In the atmosphere, using metal Ca or CaH2 Due to its strong reducing property, it undergoes redox reaction with metal oxides to generate the desired SmFeN powder.

[0019] Preferably, the median particle size D50 of the SmFeN powder is 30-60 μm, for example, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm or 60 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] Preferably, the amount of SmFeN powder is 10-500 g, for example, 10 g, 50 g, 100 g, 150 g, 200 g, 250 g, 300 g, 350 g, 400 g, 450 g or 500 g, more preferably 50-200 g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] Preferably, the amount of butylated hydroxytoluene is 0.1%-10% of the mass of the SmFeN powder, for example, it can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, and more preferably 3%-10%, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0022] Preferably, the amount of the zirconium coupling agent is 0.5%-5% of the mass of the SmFeN powder, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] Preferably, the zirconium coupling agent includes a zirconium aluminate coupling agent.

[0024] Preferably, before adding the SmFeN powder, the process further comprises adding steel balls and deionized water into the ball mill in sequence.

[0025] Preferably, the average diameter of the steel balls is 2-10 mm, for example, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, 5.5 mm, 6 mm, 6.5 mm, 7 mm, 7.5 mm, 8 mm, 8.5 mm, 9 mm, 9.5 mm or 10 mm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] Preferably, the mass ratio of the steel ball to the SmFeN powder is (100-300):1, for example, it can be 100:1, 120:1, 140:1, 160:1, 180:1, 200:1, 220:1, 240:1, 260:1, 280:1 or 300:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the mass ratio of the deionized water to the SmFeN powder is (50-150):1, for example, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, 110:1, 120:1, 130:1, 140:1 or 150:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] Preferably, the ball milling includes high-frequency ball milling and low-frequency ball milling performed sequentially.

[0029] Preferably, during the low-frequency ball milling process, butylated hydroxytoluene and a zirconium coupling agent are added to the ball mill in batches.

[0030] Preferably, the ball milling frequency of the high-frequency ball mill is 5-10 Hz, for example, it can be 5 Hz, 5.5 Hz, 6 Hz, 6.5 Hz, 7 Hz, 7.5 Hz, 8 Hz, 8.5 Hz, 9 Hz, 9.5 Hz or 10 Hz, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the milling time of the high-frequency ball milling is 1-20 h, for example, it can be 1 h, 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h or 20 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, the ball milling frequency of the low-frequency ball milling is 1-4 Hz, for example, 1 Hz, 1.5 Hz, 2 Hz, 2.5 Hz, 3 Hz, 3.5 Hz or 4 Hz, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] Preferably, the milling time of the low-frequency ball milling is 20-60 min, for example, it can be 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] Preferably, during the low-frequency ball milling process, butylated hydroxytoluene and the zirconium coupling agent are added in batches every 5-15 minutes, for example, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes or 15 minutes, but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0035] Preferably, the butylated hydroxytoluene and the zirconium coupling agent are added in batches ≥ 4 times, for example, 4 times, 5 times, 6 times, 7 times or 8 times, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, the discharging includes solid-liquid separation of the material obtained by ball milling to obtain water and slurry.

[0037] Preferably, the drying comprises vacuum drying.

[0038] Preferably, the absolute pressure of the vacuum drying is 0.05-0.2 Pa, for example, it can be 0.05 Pa, 0.06 Pa, 0.08 Pa, 0.1 Pa, 0.12 Pa, 0.14 Pa, 0.16 Pa, 0.18 Pa or 0.2 Pa, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] Preferably, the vacuum drying temperature is 30-200°C, for example, it can be 30°C, 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C or 200°C, and is more preferably 50-100°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] Preferably, the vacuum drying time is 0.5-1.5 h, for example, it can be 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h or 1.5 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] Preferably, the drying further comprises storing and testing the obtained powder.

[0042] As a preferred technical solution of the first aspect of the present invention, the coating method comprises the following steps:

[0043] (1) Taking materials: taking 50-200 g of SmFeN powder with a median particle size D50=30-60 μm, and taking butylated hydroxytoluene and zirconium aluminate coupling agent, wherein the amount of butylated hydroxytoluene taken is 3%-10% of the mass of the SmFeN powder, and the amount of zirconium aluminate coupling agent taken is 0.5%-5% of the mass of the SmFeN powder; the SmFeN powder is prepared by a reduction diffusion method;

[0044] (2) Adding materials: first, steel balls and deionized water are sequentially added to the ball mill, and then SmFeN powder is added. The average diameter of the steel balls is 2-10 mm, the mass ratio of the steel balls to the SmFeN powder is (100-300):1, and the mass ratio of the deionized water to the SmFeN powder is (50-150):1;

[0045] (3) ball milling: after the SmFeN powder is preliminarily mixed with steel balls and deionized water, high-frequency ball milling is first performed at a frequency of 5-10 Hz for 1-20 hours in a ball mill, and then low-frequency ball milling is performed at a frequency of 1-4 Hz for 20-60 minutes. During the low-frequency ball milling process, butylated hydroxytoluene and zirconium aluminate coupling agent are added in batches every 5-15 minutes, and the concentration of butylated hydroxytoluene in each batch of the ball milled material is ≤0.02wt%, and the number of batch additions is ≥4 times;

[0046] (4) Discharging: solid-liquid separation of the material obtained by ball milling to obtain water and slurry;

[0047] (5) Drying: The obtained slurry is vacuum dried at 50-100° C. for 0.5-1.5 h under an absolute pressure of 0.05-0.2 Pa to obtain an oxidation-resistant coated SmFeN powder;

[0048] (6) Save and test.

[0049] In a second aspect, the present invention provides an oxidation-resistant coated SmFeN powder, wherein the oxidation-resistant coated SmFeN powder is prepared by the coating method described in the first aspect.

[0050] In a third aspect, the present invention provides an application of the oxidation-resistant coated SmFeN powder as described in the second aspect, wherein the oxidation-resistant coated SmFeN powder is used as a permanent magnet material.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] (1) In the present invention, butylated hydroxytoluene is added to the SmFeN powder obtained by the reduction diffusion method during the ball milling process, which fully reduces the activity of the powder and prevents the powder from reacting violently after contacting the air, thereby improving the safety of the product;

[0053] (2) The present invention also adds a zirconium coupling agent to the SmFeN powder during the ball milling process, which significantly promotes the full combination of inorganic and organic matter. Compared with the traditional silane coupling agent, the inorganic part of the zirconium coupling agent has a higher specific gravity, which significantly reduces the viscosity of the powder after coating, thereby improving the powder fluidity. At the same time, due to the high metallicity of the zirconium coupling agent, the binding force between butylated hydroxytoluene and the metal is greatly increased, thereby significantly improving the coating effect.

[0054] (3) In the present invention, butylated hydroxytoluene and zirconium coupling agent are added in batches during the ball milling process, and the concentration of butylated hydroxytoluene in each batch in the ball milling material is controlled to be ≤0.02wt%, which is beneficial to significantly improve the coating effect of the anti-oxidation layer on the surface of the SmFeN powder, avoid the introduction of phenol odor due to excessive concentration, and improve the operation safety;

[0055] (4) The coating method provided by the present invention can coat finer SmFeN powder, while ensuring the performance of SmFeN, avoiding dangers in the production process, simplifying the preparation process, reducing production costs, and facilitating large-scale promotion and application. DETAILED DESCRIPTION

[0056] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0057] Example 1

[0058] This embodiment provides an anti-oxidation coated SmFeN powder and a coating method thereof, the coating method comprising the following steps:

[0059] (1) Material preparation: 100 g of SmFeN powder with a median particle size D50 = 40 μm, 4 g of butylated hydroxytoluene and 4 g of zirconium aluminate coupling agent UP-801 were taken; the SmFeN powder was prepared by the reduction diffusion method disclosed in Example 1 of CN1424165A;

[0060] (2) Adding materials: First, add 20 kg of steel balls and 10 kg of deionized water to the ball mill in sequence, and then add SmFeN powder, and the average diameter of the steel balls is 5 mm;

[0061] (3) Ball milling: After the SmFeN powder is preliminarily mixed with steel balls and deionized water, it is first subjected to high-frequency ball milling at a frequency of 8 Hz for 10 h in a ball mill, and then subjected to low-frequency ball milling at a frequency of 2 Hz for 40 min. During the low-frequency ball milling process, 1 g of butylated hydroxytoluene and 1 g of zirconium aluminate coupling agent UP-801 are added in batches every 10 min. The concentration of butylated hydroxytoluene in each batch of the ball milled material is 0.01 wt%, and the mixture is added in 4 batches in total.

[0062] (4) Discharging: filtering the material obtained by ball milling to obtain water and slurry;

[0063] (5) Drying: The obtained slurry was vacuum dried at 80° C. for 1 h under an absolute pressure of 0.1 Pa to obtain an oxidation-resistant coated SmFeN powder;

[0064] (6) Store at room temperature and pressure under nitrogen atmosphere and take samples for testing.

[0065] Example 2

[0066] This embodiment provides an anti-oxidation coated SmFeN powder and a coating method thereof, the coating method comprising the following steps:

[0067] (1) Material preparation: 50 g of SmFeN powder with a median particle size D50 = 30 μm, 2 g of butylated hydroxytoluene and 2 g of zirconium aluminate coupling agent UP-801 were taken; the SmFeN powder was prepared by the reduction diffusion method disclosed in Example 1 of CN1424165A;

[0068] (2) Adding materials: First, 15 kg of steel balls and 7.5 kg of deionized water were added to the ball mill in sequence, and then SmFeN powder was added, and the average diameter of the steel balls was 2 mm;

[0069] (3) Ball milling: After the SmFeN powder is preliminarily mixed with steel balls and deionized water, it is first subjected to high-frequency ball milling at a frequency of 5 Hz for 20 h in a ball mill, and then subjected to low-frequency ball milling at a frequency of 1 Hz for 60 min. During the low-frequency ball milling process, 0.5 g of butylated hydroxytoluene and 0.5 g of zirconium aluminate coupling agent UP-801 are added in batches every 15 min. The concentration of butylated hydroxytoluene in each batch in the ball milled material is 0.007 wt %, and it is added in 4 batches in total.

[0070] (4) Discharging: filtering the material obtained by ball milling to obtain water and slurry;

[0071] (5) Drying: The obtained slurry was vacuum dried at 100° C. for 0.5 h under an absolute pressure of 0.2 Pa to obtain an oxidation-resistant coated SmFeN powder;

[0072] (6) Store at room temperature and pressure under nitrogen atmosphere and take samples for testing.

[0073] Example 3

[0074] This embodiment provides an anti-oxidation coated SmFeN powder and a coating method thereof, the coating method comprising the following steps:

[0075] (1) Material preparation: 200 g of SmFeN powder with a median particle size D50=60 μm, 20 g of butylated hydroxytoluene and 10 g of zirconium aluminate coupling agent UP-801 were taken; the SmFeN powder was prepared by the reduction diffusion method disclosed in Example 1 of CN1424165A;

[0076] (2) Adding materials: First, add 20 kg of steel balls and 10 kg of deionized water to the ball mill in sequence, and then add SmFeN powder, and the average diameter of the steel balls is 10 mm;

[0077] (3) Ball milling: After the SmFeN powder is preliminarily mixed with steel balls and deionized water, it is first subjected to high-frequency ball milling at a frequency of 10 Hz for 1 hour in a ball mill, and then subjected to low-frequency ball milling at a frequency of 4 Hz for 50 minutes. During the low-frequency ball milling process, 2 g of butylated hydroxytoluene and 1 g of zirconium aluminate coupling agent UP-801 are added in batches every 5 minutes. The concentration of butylated hydroxytoluene in each batch of the ball milled material is 0.02 wt%, and the mixture is added in 10 batches in total.

[0078] (4) Discharging: filtering the material obtained by ball milling to obtain water and slurry;

[0079] (5) Drying: The obtained slurry was vacuum dried at 50° C. for 1.5 h under an absolute pressure of 0.05 Pa to obtain an oxidation-resistant coated SmFeN powder;

[0080] (6) Store at room temperature and pressure under nitrogen atmosphere and take samples for testing.

[0081] Example 4

[0082] The present embodiment provides an anti-oxidation coated SmFeN powder and a coating method thereof. In the coating method, except that the low-frequency ball milling in step (3) is changed to adding 0.5 g of butylated hydroxytoluene in batches every 10 minutes, a total of 2 g of butylated hydroxytoluene is added in 4 batches, the remaining steps and conditions are the same as those in Example 1, and therefore are not described here.

[0083] Example 5

[0084] The present embodiment provides an anti-oxidation coated SmFeN powder and a coating method thereof. In the coating method, except that the low-frequency ball milling in step (3) is changed to adding 3 g of butylated hydroxytoluene in batches every 10 minutes, a total of 12 g of butylated hydroxytoluene is added in 4 batches, the remaining steps and conditions are the same as those in Example 1, and therefore are not described here.

[0085] Example 6

[0086] The present embodiment provides an anti-oxidation coated SmFeN powder and a coating method thereof. In the coating method, except that the low-frequency ball milling in step (3) is changed to adding 0.5 g of zirconium aluminate coupling agent UP-801 in batches every 10 minutes, a total of 2 g of zirconium aluminate coupling agent UP-801 is added in 4 batches, the remaining steps and conditions are the same as those in Example 1, and therefore are not described here.

[0087] Example 7

[0088] The present embodiment provides an anti-oxidation coated SmFeN powder and a coating method thereof. In the coating method, except that the low-frequency ball milling in step (3) is changed to adding 3 g of zirconium aluminate coupling agent UP-801 in batches every 10 minutes, a total of 12 g of zirconium aluminate coupling agent UP-801 is added in 4 batches, the remaining steps and conditions are the same as those in Example 1, and therefore are not described here.

[0089] Comparative Example 1

[0090] This comparative example provides an anti-oxidation coated SmFeN powder and a coating method thereof. In the coating method, except that the low-frequency ball milling in step (3) is changed to a one-time addition of 4 g of dibutylhydroxytoluene and 4 g of zirconium aluminate coupling agent UP-801, the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.

[0091] Comparative Example 2

[0092] This comparative example provides an anti-oxidation coated SmFeN powder and a coating method thereof. In the coating method, except that the high-frequency ball milling in step (3) is changed to adding 1g of dibutylhydroxytoluene and 1g of zirconium aluminate coupling agent UP-801 in batches every 2.5h, and no additives are added during the low-frequency ball milling process, the remaining steps and conditions are the same as those in Example 1, and are not described here.

[0093] Comparative Example 3

[0094] This comparative example provides a SmFeN powder and a coating method thereof. The coating method is the same as Example 1 except that butylated hydroxytoluene is not added during the ball milling process in step (3). Therefore, no further description is given here.

[0095] Comparative Example 4

[0096] This comparative example provides a SmFeN powder and a coating method thereof. The coating method is the same as Example 1 except that the zirconium aluminate coupling agent UP-801 is not added during the ball milling process in step (3). The remaining steps and conditions are the same as those in Example 1, so they are not described here in detail.

[0097] Comparative Example 5

[0098] This comparative example provides a SmFeN powder and a coating method thereof. In the coating method, except that the zirconium aluminate coupling agent UP-801 is replaced with an equal mass of silane coupling agent KH560, the remaining steps and conditions are the same as those in Example 1, so they are not described in detail here.

[0099] The oxygen content, nitrogen content, D50, average thickness of the coating film and intrinsic coercivity of the SmFeN powders obtained in Examples 1-7 and Comparative Examples 1-5 were tested respectively. The oxygen content was used to characterize the degree of oxidation, the nitrogen content was used to characterize the nitriding effect, the D50 was used to characterize the powder particle size after ball milling, and the intrinsic coercivity was used to characterize the magnetic powder performance after ball milling. The relevant test results are shown in Table 1 below.

[0100] Table 1

[0101]

[0102] In Table 1 above, the test method for oxygen content and nitrogen content is obtained by CONH gas analysis; D50 is measured by a laser particle size analyzer; the average thickness of the coating film is measured based on SEM electron microscope photos; and the test method for intrinsic coercivity is NIM-2000 tester.

[0103] From Table 1, we can see that:

[0104] (1) The oxygen content of the SmFeN powder obtained by the coating method provided in Examples 1-3 is 1.45-1.47wt%, the nitrogen content is 3.1-3.13wt%, the powder particle size D50 is 1.51-1.56μm, the average thickness of the coating film is 0.56-0.58μm, the degree of oxidation of the powder is low, no explosion occurs during the preparation process, and the intrinsic coercive force of the SmFeN powder is ≥14.65KOe. It can be seen that the coating method provided by the present invention ensures the activity and magnetism of the product while effectively improving the product safety.

[0105] (2) Compared with Example 1, the amount of butylated hydroxytoluene added in Example 4 during the ball milling process is too little, while the amount of butylated hydroxytoluene added in Example 5 is too much, both of which are not conducive to further improving the magnetic properties of the SmFeN powder.

[0106] (3) Compared with Example 1, the amount of zirconium aluminate coupling agent UP-801 added in Example 6 during the ball milling process is too small, which is not conducive to further improving the magnetic properties of the SmFeN powder; while the amount of zirconium aluminate coupling agent UP-801 added in Example 7 is too large, which does not affect the thickness and magnetic properties of the coating film, but significantly increases the production cost.

[0107] (4) Compared with Example 1, in Comparative Example 1, butylated hydroxytoluene and zirconium aluminate coupling agent UP-801 were added at one time during the low-frequency ball milling process, which affected the coating effect and was not conducive to improving the magnetic properties of SmFeN powder.

[0108] (5) Compared with Example 1, in Comparative Example 2, butylated hydroxytoluene and zirconium aluminate coupling agent UP-801 were directly added during the high-frequency ball milling process, which was not conducive to the formation of the coating film and reduced the magnetic properties of the SmFeN powder.

[0109] (6) Compared with Example 1, Comparative Example 3 did not add butylated hydroxytoluene during the ball milling process, and the powder was extremely active, and severe oxidation and combustion occurred during the preparation. Comparative Example 4 did not add zirconium aluminate coupling agent UP-801, and the coating effect was greatly reduced, which greatly affected the magnetic properties of the SmFeN powder.

[0110] (7) Compared with Comparative Example 4, the addition of silane coupling agent KH560 in Comparative Example 5 does make the coating effect better, but the effect is far less than that of zirconium aluminate coupling agent UP-801 in Example 1.

[0111] It can be seen that in the present invention, butylated hydroxytoluene is added to the SmFeN powder obtained by the reduction diffusion method during the ball milling process, which fully reduces the activity of the powder and avoids a violent reaction after contacting the air, thereby improving the safety of the product; a zirconium coupling agent is also added to the SmFeN powder during the ball milling process, which significantly promotes the full combination of inorganic and organic matter, and compared with the traditional silane coupling agent, the inorganic part of the zirconium coupling agent has a large specific gravity, which significantly reduces the viscosity of the powder after coating, thereby improving the fluidity of the powder, and at the same time, due to the high metallicity of the zirconium coupling agent, the binding force between butylated hydroxytoluene and the metal is greatly increased, thereby significantly improving the coating effect; butylated hydroxytoluene and the zirconium coupling agent are added in batches during the ball milling process, and the concentration of each batch of butylated hydroxytoluene in the ball milling material is controlled to be ≤0.02wt%, which is beneficial to significantly improve the coating effect of the anti-oxidation layer on the surface of the SmFeN powder, avoid the introduction of phenol odor due to excessive concentration, and improve the operation safety.

[0112] In addition, the coating method provided by the present invention can coat finer SmFeN powder, while ensuring the performance of SmFeN, avoiding dangers in the production process, simplifying the preparation process, reducing production costs, and facilitating large-scale promotion and application.

[0113] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A coating method for anti-oxidation coated SmFeN powder, characterized in that: The coating method comprises taking materials, adding materials, ball milling, discharging materials and drying in sequence; The materials involved in the material extraction include SmFeN powder, dibutyl hydroxytoluene and a zirconium coupling agent, and the SmFeN powder is prepared by a reduction diffusion method; The adding of materials comprises adding SmFeN powder into the ball mill; The ball milling comprises adding butylated hydroxytoluene and a zirconium coupling agent into a ball mill in batches, and the concentration of butylated hydroxytoluene in each batch in the ball milling material is ≤0.02wt%.

2. The coating method according to claim 1, characterized in that: The median particle size of the SmFeN powder is D50=30-60 μm; Preferably, the amount of the SmFeN powder is 10-500 g, more preferably 50-200 g.

3. The coating method according to claim 2, characterized in that: The amount of butylated hydroxytoluene is 0.1%-10% of the mass of the SmFeN powder, and more preferably 3%-10%; Preferably, the amount of the zirconium coupling agent is 0.5%-5% of the mass of the SmFeN powder; Preferably, the zirconium coupling agent includes a zirconium aluminate coupling agent.

4. The coating method according to any one of claims 1 to 3, characterized in that: The SmFeN powder further comprises adding steel balls and deionized water into the ball mill in sequence before adding the materials; Preferably, the average diameter of the steel balls is 2-10 mm; Preferably, the mass ratio of the steel ball to the SmFeN powder is (100-300):1; Preferably, the mass ratio of the deionized water to the SmFeN powder is (50-150):

1.

5. The coating method according to any one of claims 1 to 4, characterized in that: The ball milling includes high-frequency ball milling and low-frequency ball milling performed sequentially; Preferably, during the low-frequency ball milling process, butylated hydroxytoluene and a zirconium coupling agent are added to the ball mill in batches.

6. The coating method according to claim 5, characterized in that: The ball milling frequency of the high-frequency ball milling is 5-10 Hz; Preferably, the high-frequency ball milling time is 1-20h; Preferably, the ball milling frequency of the low-frequency ball milling is 1-4 Hz; Preferably, the low-frequency ball milling time is 20-60 min; Preferably, during the low-frequency ball milling process, butylated hydroxytoluene and zirconium coupling agent are added in batches every 5-15 minutes; Preferably, the butylated hydroxytoluene and the zirconium coupling agent are added in batches ≥ 4 times.

7. The coating method according to any one of claims 1 to 6, characterized in that: The discharging includes solid-liquid separation of the material obtained by ball milling to obtain water and slurry; Preferably, the drying comprises vacuum drying; Preferably, the absolute pressure of the vacuum drying is 0.05-0.2 Pa; Preferably, the vacuum drying temperature is 30-200°C, more preferably 50-100°C; Preferably, the vacuum drying time is 0.5-1.5h; Preferably, the drying further comprises storing and testing the obtained powder.

8. The coating method according to any one of claims 1 to 7, characterized in that: The coating method comprises the following steps: (1) Taking materials: taking 50-200 g of SmFeN powder with a median particle size D50=30-60 μm, and taking butylated hydroxytoluene and zirconium aluminate coupling agent, wherein the amount of butylated hydroxytoluene taken is 3%-10% of the mass of the SmFeN powder, and the amount of zirconium aluminate coupling agent taken is 0.5%-5% of the mass of the SmFeN powder; the SmFeN powder is prepared by a reduction diffusion method; (2) Adding materials: first, steel balls and deionized water are sequentially added to the ball mill, and then SmFeN powder is added. The average diameter of the steel balls is 2-10 mm, the mass ratio of the steel balls to the SmFeN powder is (100-300):1, and the mass ratio of the deionized water to the SmFeN powder is (50-150):1; (3) ball milling: after the SmFeN powder is preliminarily mixed with steel balls and deionized water, high-frequency ball milling is first performed at a frequency of 5-10 Hz for 1-20 hours in a ball mill, and then low-frequency ball milling is performed at a frequency of 1-4 Hz for 20-60 minutes. During the low-frequency ball milling process, butylated hydroxytoluene and zirconium aluminate coupling agent are added in batches every 5-15 minutes, and the concentration of butylated hydroxytoluene in each batch of the ball milled material is ≤0.02wt%, and the number of batch additions is ≥4 times; (4) Discharging: solid-liquid separation of the material obtained by ball milling to obtain water and slurry; (5) Drying: The obtained slurry is vacuum dried at 50-100° C. for 0.5-1.5 h under an absolute pressure of 0.05-0.2 Pa to obtain an oxidation-resistant coated SmFeN powder; (6) Save and test.

9. An oxidation-resistant coated SmFeN powder, characterized in that: The anti-oxidation coated SmFeN powder is prepared by the coating method according to any one of claims 1 to 8.

10. An application of the oxidation-resistant coated SmFeN powder as claimed in claim 9, characterized in that: The oxidation-resistant coated SmFeN powder is used as a permanent magnetic material.

Citation Information

Patent Citations

  • Preparation method of magnetic ceramic-coated SmFeN permanent magnet material

    CN105702407A

  • Method for producing Sm-Fe-N permanent magnet alloy powder by reduction diffusion

    CN1424165A